Nuclear power plant life management and longer-term operation (Nuclear development., 2006)
This book, prepared by NEA member country experts, contains data and analyses relevant to nuclear power plant life management and the plants extended, longer-term operation (LTO). It addresses technical, economic and environmental aspects and provides insights into the benefits and challenges of plant life management and LTO.--Publisher's description.